Lean premixed combustion models at elevated pressure for the gas turbine - Wood, J. P. (Cranfield University, 2004)
The latter half of the 20th century has seen great strides made in understanding premixed combustion, and this combined with advances in computing, has lead to significantly improved combustion models. Over the same period changes in the international energy market, allied with major technological advances, have promoted gas turbines to the forefront of power generation. Lean premixed combustion is key to the low emissions produced in such devices, but with ever more stringent emissions regulations burner design becomes increasingly vital. However there has, perhaps, been a lack of emphasis on research areas that directly influence practical burner design. In particular it is possible to identify high pressure combustion and the development of models that address the pragmatic requirements of industry as areas that have received insufficient attention. This study aims to examine the effectiveness, at elevated pressure, of two models that appear to better meet the demands of industry. The selected models are the turbulent flame speed closure and fractal models. These are implemented in a novel partially premixed form within the CFD research code SOFIE. Comparisons are made between measurements, made by applying particle image velocimetry in a novel manner, and predictions in order to determine the accuracy of these models. The principal conclusion was that although the turbulent flame speed closure model replicated the experimental measurements surprisingly well the fractal model did not. However, a major weakness was identified in extending premixed combustion models, based on the concept of a progress variable, to partially premixed problems. This weakness introduced significant errors into prediction of the fuel distribution, which at the extreme could lead to the apparent 'creation' of fuel. No simple solution to this problem is immediately apparent, and hence it is argued alternative approaches, based on the techniques used in diffusion flames, should be investigated.